The Problem of Happiness in the Philosophical views of Abu Ali Ibn Sina (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This scientific article focuses on the great philosopher Abu Ali ibn Sina, who lived and worked in the X-XI centuries, on the issue of happiness in achieving philosophical, moral, and human perfection, and argues that the issues of well-being and happiness are of paramount importance today. In today's globalized world, it is becoming increasingly important to study, research and inform the general public about the teachings and scientific heritage of our great scientists who lived and worked in the past. As Ibn Sina puts forward his philosophical views on Al-Isharat wa at-Tanbihot and its bliss, it can be seen that it reflects the image of true happiness. The "Happiness" section of this work provides an in-depth analysis of the philosophical aspects of the pursuit of happiness, comparing the understanding of what happiness is for a prosperous life, the superiority of inner pleasure over external pleasure in the matter of happiness.